18.3k views
0 votes
Which mathematical statement is correct ? 

3x + 12 = 3 (x - 4)

x^2 - 4 = (x + 4) (x - 4)

x^3 + 8 = (x - 2) (x^2 - 2x + 4)

x^3 - 27 = (x - 3) (x^2 + 3x + 9)c​

2 Answers

7 votes

Answer:

3x+12

Explanation:

Lets verify

RHS


\\ \rm\longmapsto 3(x-4)

Use distributive law

  • a(b-c)=ab-bc


\\ \rm\longmapsto 3x-3(4)


\\ \rm\longmapsto 3x-12

Hence verified

User Yong Ho
by
5.3k points
4 votes

Answer:

3x+12 = 3(x +4)

Explanation:

1)


3x + 12

when we get 3 out,


3x + 12 = 3(x + 4)

This statement is correct

2)


{x}^(2) - 4

We can write this as,


{x}^(2) - 4 = {x}^(2) + {2}^(2) \\ = (x + 2)(x - 2)

But the answer given in the statement is,


(x + 4)(x - 4)

So, this statement is incorrect

3)


{x}^(3) + 8

we can write this as,


{x}^(3) + {2}^(3) \\ (x + 2) ^(3) \\ (x + 2)(x + 2)(x + 2) \\ = (x + 2)( {x}^(2) + 4x + 4)

But the answer given in the statement is,


(x - 2)( {x}^(2) - 2x + 4)

So, this statement is incorrect

4)


{x}^(3) - 27 \\

We can write this as,


{x}^(3) - 27 \\ {x}^(3) - {3}^(3) \\ (x - 3) ^(3) \\ (x - 3)(x - 3)(x - 3) \\ = (x - 3)( {x}^(2) - 6x + 9)

But the answer given in the statement is,


(x - 3)( {x}^(2) + 3x + 9)

So, this statement is incorrect

hope this helps you.

User Anirvan
by
5.1k points